Challenges and coping strategies of Malaysian untrained EFL Orang Asli preschool teachers - Nur 'Ainin Sofiya Rosman,; Manjet Kaur Mehar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study addresses the pressing challenges faced by untrained Orang Asli preschool teachers in rural Perak, Malaysia, as they deliver English as a foreign language in resource-constrained educational settings. The primary objective is to explore the key barriers these teachers encounter and the coping strategies they employ to navigate such challenges, thereby gaining a more profoun insight into their instructional realities. Using a qualitative case study approach, data were gathered through semi-structured focus group discussions involving twelve untrained teachers from five Orang Asli preschools. The analysis reveals that limited English proficiency, absence of formal pedagogical training, insufficient teaching materials and infrastructure, as well as sociocultural resistance within the community, constitute significant impediments to effective English language instruction. Despite these multifaceted obstacles, the teachers demonstrate commendable resilience and agency by actively engaging in peer collaboration, forming informal support networks, and creatively improvising with available resources to facilitate early language learning. These adaptive strategies illuminate their ability to respond pragmatically to systemic educational inequities and acute resource limitations. The findings underscore an urgent need for culturally responsive professional development programmes, context-specific and culturally relevant teaching materials, and comprehensive systemic support services co-designed with Orang Asli communities. By foregrounding the lived experiences and voices of untrained Orang Asli preschool teachers, this research advances understanding of Indigenous educational equity and offers practical, actionable recommendations for educational policy and practice aimed at reducing long-standing disparities within Indigenous communities.